The experience of using the placenta hydrolyzate in women with climacteric syndrome in perimenopausal period - I I Kovalenko; A V Atalyan (IP Berlin A.V., 2016)
This article presents the results of randomized, blind, placebo-controlled prospective study in parallel groups. 40 premenopausal women with symptoms of climacteric syndrome, menstrual disordersand FSH level more than 20 mIu/ml, were recruited and randomized into 2 groups: 20 women (group 1) used placenta extract Melsmon (Japan), 2 ml (100 mg), subcutaneously, every 2nd day for 2 weeks, then 2 time a week (30 injections for 4 months in total). 20 patients (group 2) were included in the placebo group (2 ml subcutaneously, in similar regimen). After 4 months of treatment the significant decrease of modified Kupperman menopausal index, decrease of time required tofall asleep and night time awakenings number, as far as increasing of sleep duration and significant improvement of general health self-assessment were registered in both groups. The improvement of psycho-emotional symptomsand skin condition after intervention was reported only in the 1st group. 32% of women used placental extract and 5% patients from placebo group reported about menstrual episodes after period of amenorrhea, without any significant changes in endometrial thickness. Study limitations: because of the small sample size and limited observation period, more long-term trials are needed.